Digestive protease activities, growth and feed utilisation in Atlantic salmon (Salmo salar L.) - Sunde, Jan (The University of Bergen, 2006)
This dissertation consists of the following papers, referred to in the text by their Roman numerals. The specific activities of trypsin and chymotrypsin in the pyloric caeca were investigated in individually labeled Atlantic salmon (Salmo salar L.). Photoperiod (natural or 24 h) and feed protein quality (two levels of digestibility) were used as growth affecting factors in two grow-out experiments. Parameters indicative of protein growth and metabolism, i.e. plasma and white muscle free amino acid (FAA) concentrations, white muscle RNA concentrations, and white muscle protein synthesis capacity (RNA/protein ratio) were also measured. The feasibility of using free hydroxyproline (Hyp) concentration in the white muscle as an indicator of the rate of tissue protein breakdown (turnover) was assessed. Further, an in vitro digestibility assay was developed to evaluate the effects of industrial processing conditions on feed protein digestibility. Digestion using crude pyloric caecal extracts was standardised by trypsin activity and compared with growth experiments to predict the effects of feed protein quality on specific growth rate (SGR) and feed conversion efficiency (FCE). Finally, dorsal aorta cannulation of fish was assessed as a tool for evaluating feed protein quality (containing no free or supplemented amino acids) through repeated measurements of plasma FAA concentrations after feeding. Trypsin (T) and chymotrypsin (C) showed high covariation in all experiments, regardless of whether growth was affected indirectly (through photoperiod manipulation) or directly (through feed protein quality). Groups exhibiting different feed conversion efficiencies (FCE) had different activity ratios of trypsin to chymotrypsin (T/C ratio). The T/C ratio seemed to be more sensitive than growth measurements to slight differences in feed protein quality and might have an application as an indicator of growth performance. In salmon reared under different photoperiods, SGR correlated with trypsin activity and T/C ratio on ...